2005
DOI: 10.1097/01.fjc.0000171753.43564.7c
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines Inhibit Both Platelet Aggregation and Glycoprotein IIb/IIIa Activation

Abstract: Platelet aggregation is inhibited by the polyamines putrescine, spermidine, and spermine. To date, the mechanism of action has not been clearly identified. Evidence suggests that polyamines may interact with the fibrinogen receptor (GP IIb/IIIa), interfering with platelet-platelet attachment. The effect of polyamines on human platelet aggregation and GP IIb/IIIa activation was evaluated. For the aggregation experiments, platelets were obtained from heparin- or citrate-collected blood. Our results indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
3
9
0
Order By: Relevance
“…The results also demonstrate that polyamines exert no physiologically significant difference on basal electrogenic secretion than controls. Many of the physiological properties of polyamines appear to be linked with their valency -this was shown in the results of the Ussing chamber studies as well as cAMP quantification, and parallels with findings from other functional studies (Cheng et al, 2004;Corona-de-la-Pena et al, 2005).…”
Section: Discussionsupporting
confidence: 62%
“…The results also demonstrate that polyamines exert no physiologically significant difference on basal electrogenic secretion than controls. Many of the physiological properties of polyamines appear to be linked with their valency -this was shown in the results of the Ussing chamber studies as well as cAMP quantification, and parallels with findings from other functional studies (Cheng et al, 2004;Corona-de-la-Pena et al, 2005).…”
Section: Discussionsupporting
confidence: 62%
“…Since polyamines have been reported to inhibit platelet aggregation [30], we examined whether polyamines modulate system y + L activity. Following incubation of platelet suspensions with increasing concentrations of putrescine (2–10 µ M ), L -arginine influx (1 µ M ) was unchanged (n = 5) (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…30 Our finding that spermine, norspermine, and spermidine are potent polyP inhibitors is noteworthy because the naturally occurring polyamines, spermine, spermidine, and putrescine inhibit aggregation of human platelets, [31][32][33][34][35][36][37] and systemic administration of polyamines is reported to prevent carotid artery occlusion in a canine thrombosis model. 38 The latter investigators concluded that the antithrombotic activity of polyamines was the result of inhibition of platelet aggregation, although it is tempting to speculate that inhibition of platelet-secreted polyP procoagulant activity may have also contributed to their protective effects.…”
Section: Discussionmentioning
confidence: 99%